GPS Signal Corruption by the Discrete Aurora: Precise Measurements From the Mahali Experiment. Issue 19 (5th October 2017) - Semeter, Joshua; Mrak, Sebastijan; Hirsch, Michael; Swoboda, John; Akbari, Hassan; Starr, Gregory; Hampton, Don; Erickson, Philip; Lind, Frank; Coster, Anthea; Pankratius, Victor
Abstract: Measurements from a dense network of GPS receivers have been used to clarify the relationship between substorm auroras and GPS signal corruption as manifested by loss of lock on the received signal. A network of nine receivers was deployed along roadways near the Poker Flat Research Range in central Alaska, with receiver spacing between 15 and 30 km. Instances of large‐amplitude phase fluctuations and signal loss of lock were registered in space and time with auroral forms associated with a sequence of westward traveling surges associated with a substorm onset over central Canada. The following conclusions were obtained: (1) The signal corruption originated in the ionospheric E region, between 100 and 150 km altitude, and (2) the GPS links suffering loss of lock were confined to a narrow band (<20 km wide) along the trailing edge of the moving auroral forms. The results are discussed in the context of mechanisms typically cited to account for GPS phase scintillation by auroral processes. Plain Language Summary: We deployed a network of GPS receivers to central Alaska to study the effects of the aurora on GPS signals. We mapped the locations of instances where the receiver lost lock on the GPS signal and found that these occurrences were clustered along the edges of auroral arcs associated with dynamic space weather events (in this case, during a so‐called geomagnetic substorm). The loss of signal lock was due to interactions between the GPS signal and small‐scale density irregularities in the ionosphere. This result helps us understand where these irregularities occur. Key Points: A closely spaced network of GPS receivers is used to study space‐time correlation between substorm auroral forms and loss of signal lock Loss‐of‐lock events were found to be clustered within a narrow 10 km band just outside the trailing edge of auroral forms The measurements also suggest that the density irregularities producing these extreme scintillation events are at E region altitudes